GROWTH AND YIELD OF BAMBARA GROUNDNUT AS INFLUENCED BY POULTRY MANURE RATES AND INOCULATION IN NORTHERN GUINEA SAVANNAH OF NIGERIA - Ladan, Muhammad K.; Kura, Habu Nasiru; Lawal, Abdul Bamidele (FUDMA JOURNAL OF SCIENCES, 2025)
Bambara ground nut is a nutrient-dense legume termed a “complete food” due to its balanced macronutrient composition, however poor soil fertility is one of the most important biophysical constraints to its productivity. Also, combination of nutrient demand with supply is critical for plant growth, development and yield. Therefore, this study was conducted to evaluate the effect of poultry manure and inoculation on growth and yield of Bambara groundnut during the dry season of 2020/2021 cropping season at irrigation farm of Institute for Agricultural Research IAR, A.B.U., Samaru- Zaria and College of Agriculture and Animal Science, Irrigation Farm Mando, Kaduna both located in the Northern Guinea Savannah Ecological Zone of Nigeria respectively. Treatments consisted of four rates of poultry manure (0.0, 2.0, 4.0 and 6.0) tons ha-1 and two levels of rhizobium inoculation; no inoculation and inoculation. Treatment were factorially combined in a randomized complete block design (RCBD) and replicated three times. Data on growth parameter were collected on plant height (cm), leaf Area index (LAI), Crop growth rate (CGR) Relative Growth Rate (RGR) and kernel yield kg ha-1 were collected. Results showed that 6 tons/ha poultry manure recorded significantly higher values of growth parameters like plant height (cm), leaf Area index (LAI),crop growth rate (CGR) Relative Growth Rate (RGR) and kernel yield kg ha-1 of Bambara groundnut over other rates evaluated at both locations. While inoculation of Bambara groundnut significantly resulted in higher performance in both growth and yield parameters evaluated over non-inoculated Bambara groundnut plants at both locations...